Avaliação clínica de restaurações em lesões cervicais não cariosas realizadas por diferentes operadores e estratégias adesivas: estudo multicêntrico - Martinez, Issis Virginia Luque (2015)
There is controversy over which of the adhesive strategies available today (2and 3 steps etch-and-rinse; 1 and 2 steps self-etching steps) provides a better clínical performance, identifying the importance of conducting longitudinal clínical studies to evaluate these strategies adhesive in a controlled environment and in practice daily clinic. However, there is a void in the influence of the operator. Thus, the aim of this study was to evaluate the influence of the operator's experience level (student, professional) and adhesive strategy (conventional 2:03 steps, self-etching steps 1 and 2) in the clínical performance of composite restorations in non-carious cervical lesions (NCCL) applied in models of randomized clínical trial (ECA) and Practice-based Clinic trial (ECBPC) held in two centers (Brazil and Chile), for a period of up to 6-month evaluation. A total of 185 patients with at least four NCCL were selected for the study according to the inclusion and exclusion criteria to conform 5 clínical trials: In Brazil center, 70 patients were allocated into two groups ECA (n=35), second operator: student (ECA-A-Brazil) and professional (ECA-P-Brazil); In Chile center, 80 patients conformed the ECA-A-Chile and ACE-P-Chile (n=40) and 35 patients participated in the ECBPC (only in Chile). The 4 adhesive strategies were applied at random in each patient according to the manufacturer's instructions. The restorations were assessed immediately and after 6 months performed by blind evaluators for adhesive strategy, using the FDI criteria while: fracture/retention; marginal adaptation; postoperative sensitivity; and caries adjacent to the restoration. A total of 781 restorations of composite resin were placed during the execution of five clínical trials of this project. There was 100% attendance of patients evaluations. In ECA-P-Brazil 5 restorations were lost (4.3% loss rates for FL, 2.7% for SP, 4.5% and 0.0% for XTR and AIO) and 7 restorations in ECA-A- Brazil (0.0% to FL, 3.2% for SP, 6.5% for XTR, and 12.5% for the AIO); For ECA-P-Chile, 16 restorations were lost (7.5% loss rates for FL, 7.5% for SP, 5.0% for XTR, and 20.0% for the AIO) and the ECA-A-Chile, a total of 10 restorations (12.5% for FL; 0.0% for SP, 7.5% to XTR, and 7.5% for OIA). Compared the different times for each adhesive, just was statistical difference for AIO in ECA-P-Chile and ECBPC (p=0.005). When the centers are different compared ECA-P-Chile present 3 times fall that ECA-P-Brazil (p=0.006). The adhesive technique AIO seems to have difficulties in applying for professional’s operators, having a negative influence on the retention rate. Thus longer evaluation periods are needed to clarify these differences.